2021
DOI: 10.1109/access.2021.3116809
|View full text |Cite
|
Sign up to set email alerts
|

Using Long Short-Term Memory (LSTM) and Internet of Things (IoT) for Localized Surface Temperature Forecasting in an Urban Environment

Abstract: The rising temperature is one of the key indicators of a warming climate, capable of causing extensive stress to biological systems as well as built structures.Ambient temperature collected at ground level can have higher variability than regional weather forecasts, which fail to capture local dynamics. There remains a clear need for accurate air temperature prediction at the suburban scale at high temporal and spatial resolutions. This research proposed a framework based on a long short-term memory (LSTM) dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Multiple linear regression can also be used in data analysis [53]. Currently, machine learning is commonly used to analyze sensorgenerated data [44,49,52,[55][56][57]63,[65][66][67]. The machine learning techniques include neural network [49], support vector machine [52], Long Short-Term Memory [56,67], and Random Forest [44].…”
Section: Parameter Model Referencementioning
confidence: 99%
“…Multiple linear regression can also be used in data analysis [53]. Currently, machine learning is commonly used to analyze sensorgenerated data [44,49,52,[55][56][57]63,[65][66][67]. The machine learning techniques include neural network [49], support vector machine [52], Long Short-Term Memory [56,67], and Random Forest [44].…”
Section: Parameter Model Referencementioning
confidence: 99%
“…The semantic result was IoT-based sensors and the proposed big data processing system makes it very efficient to monitor the manufacturing process [221]. Another example was proposed by Yu et al The processing is use LSTM (long short-term memory) deep learning network methods to process all IoT data and provide semantic services such as New York City temperature forecasting [222]. Besides those two computational intelligence methods, there are a lot of other methods to process and provide semantic services such as KNN [223], DTMC (Discrete-time Markov chain) [224], SNN [225], CNN [226], Random Tree [227], and more.…”
Section: F Semanticmentioning
confidence: 99%
“…Furthermore, two NN flavors are particularly well suited for ESP application due to the spatiotemporal nature of Earth system model output quantities of interest. These are recurrent NNs (RNNs) that are built to handle temporal predictions and forecasts (Vandal et al 2017;Shen, Liu, and Wang 2021;Yu et al 2021) and convolutional NNs (CNNs) that efficiently target spatial relationships and patterns (Ise and Oba 2019;Chattopadhyay, Hassanzadeh, and Pasha 2020;Steininger et al 2020;Baño-Medina, Manzanas, and Gutiérrez 2021). Finally, generative modeling approaches, such as GANs (Besombes et al 2021;Klemmer et al 2021;Wang, Tang, and Gentine 2021) and VAEs (Tibau Alberdi et al 2018;Scher 2018;Mooers et al 2020;Zadrozny et al 2021) have demonstrated early promise in the Earth sciences (e.g., ).…”
Section: State-of-the-sciencementioning
confidence: 99%